CAUSES PRIMAIRES DE LA CRIMINALITÉ ET DE LA DÉLINQUANCE JUVÉNILE - Mielke, Jana (WEB REVISTA LINGUAGEM, EDUCAÇÃO E MEMÓRIA, 2017)
This article is focused on the general primary ethiology of youth criminality and delinquency.